coil_2d.f90 1.92 KB
Newer Older
1
2
3
4
5
6
7
8
9
10
11
12
13
14
15
16
17
18
! ----------------------------------------------------------------------
      subroutine  coil_2d(xc,yc,zc,nc,cur,xb,yb,zb,phib)
! ----------------------------------------------------------------------
!
!     purpose:
!
!
! ----------------------------------------------------------------------
      implicit none
      real,dimension (  nc  ,2) :: xc ,yc ,zc
      real,dimension (2*nc-2,3) :: xb, yb ,zb, phib
      real                      :: cur,dist
      integer                   :: j,k,k1,nc
! -------- --------------------------------------------------------------
      dist =  (xc(nc,1)-xc(1,1))**2+(yc(nc,1)-yc(1,1))**2               &
             +(zc(nc,1)-zc(1,1))**2+(xc(nc,2)-xc(1,2))**2               &
             +(yc(nc,2)-yc(1,2))**2+(zc(nc,2)-zc(1,2))**2
      if(dist.gt.1.e-6) then
Serhiy Mochalskyy's avatar
Serhiy Mochalskyy committed
19
20
21
22
23
24
25
              write(6,*) dist, xc(nc,1)-xc(1,1),yc(nc,1)-yc(1,1)  &
                         ,zc(nc,1)-zc(1,1)    
              write(6,*)
              write(6,*) dist, xc(nc,2)-xc(1,2),yc(nc,2)-yc(1,2)  &
                        ,zc(nc,2)-zc(1,2)    
              write(6,*) 'coil_2d is not closed:  stop'
              stop
26
27
28
29
30
31
32
33
34
35
36
37
38
39
40
41
42
43
44
45
46
47
48
49
50
51
52
53
54
55
56
57
      endif
         j=0
      do k = 1, nc-1
               k1 = k+1
                j = j+1
          xb(j,1) = xc(k ,2)
          yb(j,1) = yc(k ,2)
          zb(j,1) = zc(k ,2)
          xb(j,2) = xc(k1,2)
          yb(j,2) = yc(k1,2)
          zb(j,2) = zc(k1,2)
          xb(j,3) = xc(k ,1)
          yb(j,3) = yc(k ,1)
          zb(j,3) = zc(k ,1)
         phib(j,1)= cur 
         phib(j,2)= cur 
         phib(j,3)=  0.
                 j=j+1
          xb(j,1) = xc(k1,1)
          yb(j,1) = yc(k1,1)
          zb(j,1) = zc(k1,1)
          xb(j,2) = xc(k ,1)
          yb(j,2) = yc(k ,1)
          zb(j,2) = zc(k ,1)
          xb(j,3) = xc(k1,2)
          yb(j,3) = yc(k1,2)
          zb(j,3) = zc(k1,2)
         phib(j,1)= 0.
         phib(j,2)= 0. 
         phib(j,3)= cur
      enddo
 end subroutine  coil_2d